2016
DOI: 10.1016/j.jpge.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan-Induced Sprue Like Enteropathy

Abstract: Chronic diarrhoea is a common clinical problem in gastroenterology practice and often it is difficult to diagnose the cause. Villous atrophy is not specific and the rarer possibility of drug-induced enteritis should always be considered. Olmesartan has recently been described as a cause of drug-induced enteropathy characterized by chronic diarrhoea and varying degrees of duodenal mucosa atrophy resembling celiac disease.We describe two cases of sprue-like enteropathy in patients treated with olmesartan for art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 7 publications
1
36
0
1
Order By: Relevance
“…Although the pathophysiology of olmesartan-associated enteropathy is unknown, it has been suggested there may be a cell-mediated immune response that damages the small intestinal brush border 2–6. Accordingly, in some studies, it has been found that people with autoimmune diseases have a higher predisposition 7 8. Severe chronic non-bloody diarrhoea and weight loss are the commonly reported symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of olmesartan-associated enteropathy is unknown, it has been suggested there may be a cell-mediated immune response that damages the small intestinal brush border 2–6. Accordingly, in some studies, it has been found that people with autoimmune diseases have a higher predisposition 7 8. Severe chronic non-bloody diarrhoea and weight loss are the commonly reported symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the case reports by da Silva et al 1 , Carneiro et al 2 and Eusébio et al 3 published in the late issue of GE Portuguese Journal of Gastroenterology .…”
mentioning
confidence: 93%
“…In this issue of GE Portuguese Journal of Gastroenterology , case reports by da Silva et al 32 , Carneiro et al 33 and Eusébio et al 34 , highlight the importance of considering sprue-like enteropathy associated with olmesartan when approaching a patient with seronegative villous atrophy and provide further information to aid in diagnosis of this emergent disease.…”
mentioning
confidence: 99%
“…In the four cases reported in this issue, symptoms resolved within 48 h to one week of discontinuation of olmesartan. 32 , 33 , 34 Trialing a patient off of a medication early on in the evaluation of seronegative villous atrophy could therefore provide both a rapid and cost-effective diagnosis. It is our practice that following olmesartan withdrawal, we try to understand the primary indication for olmesartan therapy and reassess the need for alternative medications together with the patient's primary care physician.…”
mentioning
confidence: 99%
See 1 more Smart Citation